Supporting english language learners at University of Cordoba to deal with Llack of vocabulary and confidence through meaningful mentoring strategies (2025)
This report outlines a virtual internship within the University of Córdoba’s Internship Mentoring Program, aimed at supporting five second-semester Foreign Languages students struggling with English proficiency. The internship focused on overcoming challenges like limited vocabulary, fragmented oral communication, lack of confidence, and reliance on mental translation through tailored mentoring. As a mentor, I conducted virtual sessions (60 180 minutes) using scaffolding, immediate feedback, and tools such as Postcards, Worlds, and Quizlet. Activities like role-plays, vocabulary extraction from authentic media, and guided grammar exercises promoted autonomy and fluency. Students showed marked improvement in vocabulary retention, communicative fluency, and confidence, while reducing mental translation and speaking anxiety. I developed skills in diagnostic assessment, lesson planning, empathetic communication, and virtual classroom management. The internship also highlighted the value of personalized virtual interventions within the university’s academic support system. This experience enhanced my adaptability, deepened my grasp of English language pedagogy, and strengthened my dedication to student-centered teaching, laying a robust foundation for my future as an educator.